Exome association analysis sheds light onto leaf rust (Puccinia triticina) resistance genes currently used in wheat breeding (Triticum aestivum L.). Issue 6 (20th December 2019) - Liu, Fang; Zhao, Yusheng; Beier, Sebastian; Jiang, Yong; Thorwarth, Patrick; H. Longin, C. Friedrich; Ganal, Martin; Himmelbach, Axel; Reif, Jochen C.; Schulthess, Albert W.
Summary: Resistance breeding is crucial for a sustainable control of leaf rust ( Puccinia triticina ) in wheat ( Triticum aestivum L.) while directly targeting functional variants is the Holy Grail for efficient marker‐assisted selection and map‐based cloning. We assessed the limits and prospects of exome association analysis for severity of leaf rust in a large hybrid wheat population of 1574 single‐crosses plus their 133 parents. After imputation and quality control, exome sequencing revealed 202 875 single‐nucleotide polymorphisms (SNPs) covering 19.7% of the high‐confidence annotated gene space. We performed intensive data mining and found significant associations for 2171 SNPs corresponding to 50 different loci. Some of these associations mapped in the proximity of the already known resistance genes Lr21, Lr34‐B, Lr1 and Lr10, while other associated genomic regions, such as those on chromosomes 1A and 3D, harboured several annotated genes putatively involved in resistance. Validation with an independent population helped to narrow down the list of putative resistance genes that should be targeted by fine‐mapping. We expect that the proposed strategy of intensive data mining coupled with validation will significantly influence research in plant genetics and breeding.